-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathsummary.tex
407 lines (368 loc) · 13.9 KB
/
summary.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
\documentclass[10pt]{article}
\usepackage{amsmath}
\begin{document}
\section{System}
\begin{align}
u_t &= u_{xx} + (1-v)F(w) \\
v_t &= \epsilon v_{xx} + (1-v)F(w)\\
w &= hu+(1-h)v
\end{align}
with $h \in [0,1], \epsilon \in (0,1]$.
We take a discontinuous nonlinearity
\begin{equation}
F(w) = \left\{\begin{array}{ll}
\mathrm{exp}\left(Z\left\{\frac{w-h}{\sigma+(1-\sigma)w} \right\} \right) & w \geq w^*\\
0 & w < w^*
\end{array} \right.
\end{equation}
\section{Waves}
\begin{align}
&U_{\xi\xi} + cU_\xi + (1-V)F(W) = 0\\
&\epsilon V_{\xi\xi} + cV_\xi + (1-V)F(W) = 0\\
&W = hU+(1-h)V
\end{align}
At $-\infty$, $(U,V) \to (1,1)$, and at $\infty$, $(U,V) \to (0,0)$.
In the region $W < w^*$ where $F(W) = 0$, these equations do not involve $U$ and $V$ at all---they are differential equations for $U_\xi$ and $V_\xi$.
As a result, integration may not hit $(0,0)$. To fix this, we integrate the system.
Let
\begin{equation}
z = \frac{1}{c}\int_\xi^\infty (1-V)F(W)
\end{equation}
Clearly $z=0$ at $\infty$. After integration we will get $z=1$ at $-\infty$.
This gives
\begin{equation}
z_\xi = -\frac{1}{c}(1-V)F(W)
\end{equation}
so
\begin{align}
&U_{\xi\xi}+cU_\xi-cz_\xi = 0\\
&\epsilon V_{\xi\xi}+cV_\xi-cz_\xi = 0
\end{align}
These may now be integrated.
\begin{align}
&U_\xi + cU - cz = q \\
&\epsilon V_\xi + cV - cz = r
\end{align}
where $q$ and $r$ are constants.
At $\infty$, each of $U_\xi$, $U$, and $z$ go to 0, so $q=0$.
Likewise $r=0$.
At $-\infty$, $U_\xi = 0$ and $U = 1$, so we get $z=1$.
\begin{align}
&U_\xi + cU - cz = 0 \\
&\epsilon V_\xi + cV - cz = 0
\end{align}
Thus, our end behavior is $(U,V,z) \to (1,1,1)$ at $-\infty$, and $(U,V,z) \to (0,0,0)$ at $\infty$.
\subsection{$\epsilon = 0$}
In this case, we get $V = z$, and the system is two-dimensional.
\begin{align}
U_\xi &= c(V-U) \label{front_eps0} \\
V_\xi &= - \frac{1}{c}(1-V)F(W)
\end{align}
For shooting, we want to find the positive eigendirection at $(1,1)$.
The system linearizes to
\[
\begin{bmatrix}
P\\Q
\end{bmatrix}'
=
\begin{bmatrix}
-c & c \\
-K_u/c & -K_v/c
\end{bmatrix}
\begin{bmatrix}
P\\Q
\end{bmatrix}
\]
where $K = (1-v)F(w)$.
At $(U,V) = (1,1)$ we have $K_u = 0$ and $K_v = - e^{(1-h)Z}$, so the matrix is
\[
\begin{bmatrix}
-c & c \\
0 & e^{(1-h)Z}/c
\end{bmatrix}
\]
The positive eigenvalue is $e^{(1-h)Z}/c$, with eigenvector $[1,1+e^{(1-h)Z}/c^2]$.
\subsection{$\epsilon \neq 0$}
Here the system is
\begin{align}
U_\xi &= -cU + cz \\
V_\xi &= \frac{1}{\epsilon}(-cV + cz) \\
z_\xi &= -\frac{1}{c}(1-V)F(W)
\end{align}
This linearizes to
\[
\begin{bmatrix}
P\\Q\\R
\end{bmatrix}'
=
\begin{bmatrix}
-c & 0 & c \\
0 & -c/\epsilon & c/\epsilon \\
-K_u/c & -K_v/c & 0
\end{bmatrix}
\begin{bmatrix}
P\\Q\\R
\end{bmatrix}
\]
At $(1,1)$ the matrix becomes
\[
\begin{bmatrix}
-c & 0 & c \\
0 & -c/\epsilon & c/\epsilon \\
0 & e^{(1-h)Z}/c & 0
\end{bmatrix}
\]
This has one positive eigenvalue, which is quite a mess.
We found these with computer algebra.
\[
-1/2 (c e^{Z h - Z} - \sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon e^{Z h -
Z}}) e^{-Z h + Z}/\epsilon
\]
Its eigenvector is:
\begin{multline*}
[1,\\
-\frac{1}{2} (c^2 \epsilon e^{3 Z h - Z} - c^2 e^{3 Z h -
Z} - ((\sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon e^{Z h - Z}} c + 2) \epsilon \\
- \sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon e^{Z h -
Z}} c) e^{2 Z h}) e^{-2 Z h}/\epsilon^2, \\
\frac{1}{2} ((2 c \epsilon - c) e^{Z h} +
\sqrt{c^2 e^{Z h} + 4 \epsilon e^Z} e^{1/2 Z h}) e^{-Z h}/(c \epsilon)]
\end{multline*}
\section{Finding $c$}
We find $c$ by integrating the ODE from a point close to $(1,1,1)$, in the positive eigendirection.
At different values of $c$, we end up at different points, and there's only one correct value where we hit $(0,0,0)$.
We can tell whether our value is too high or low by where the terminus is: if $c$ is too low, we finish with $U,V < 0$, and vice versa. This lets us perform a simple binary search to approach the correct value of $c$.
Starting in an eigendirection lets us approximate the ODE backward in time with simple exponential decay.
Since the $(1,1,1)$ fixed point is a saddle, backward integration eventually leaves along another eigendirection, so we do this instead.
\section{Linearization}
First, moving frame version:
\begin{align}
u_t &= u_{\xi\xi} + c u_\xi + (1-v)F(w) \\
v_t &= \epsilon v_{\xi\xi} + c v_\xi+ (1-v)F(w)
\end{align}
We linearize about the front with perturbation $(p,q)$. This gives:
\begin{align}
p_t &= p_{\xi\xi} + c p_\xi + K_u p + K_v q \\
q_t &= \epsilon q_{\xi\xi} + c q_\xi+ K_u p + K_u q
\end{align}
where $K = (1-v)F(w)$.
$K_u$ and $K_v$ are evaluated at the front.
For $w \geq w^*$, $K_u$ and $K_v$ are each messy functions of $u$ and $v$; we find them with computer algebra.
For $w < w^*$, since $F = 0$ uniformly we have $K_u = K_v = 0$.
This gives us the operator
\[
L = \begin{bmatrix}
\partial_{\xi\xi} + c \partial_\xi + K_u & K_v \\
K_u & \epsilon \partial_{\xi\xi} + c \partial_\xi + K_v
\end{bmatrix}
\]
We wish to solve $LX = \lambda X$, i.e.
\begin{align}
\lambda p &= p_{\xi\xi} + c p_\xi + K_u p + K_v q \\
\lambda q &= \epsilon q_{\xi\xi} + c q_\xi+ K_u p + K_v q
\end{align}
\subsection{$\epsilon = 0$}
We will study the $\epsilon=0$ case for now, to simplify things.
We can rewrite this as a first-order system $X' = AX$ by introducing $p_x = s$.
\begin{align}
p_\xi &= s \\
s_\xi &= \lambda p - c s - K_u p - K_v q \\
q_\xi &= (\lambda q - K_u p - K_v q)/c
\end{align}
Writing as a matrix, where $K_u$ and $K_v$ depend on the front,
\[
X = \begin{bmatrix}p\\s\\q\end{bmatrix},
A = \begin{bmatrix}
0 & 1 & 0 \\
\lambda - K_u & -c & -K_v \\
- K_u/c & 0 & (\lambda - K_v)/c
\end{bmatrix}
\]
\subsection{$\epsilon \neq 0$}
In this case, the system becomes four-dimensional, with $p_x = s$ and $q_x = r$.
(these are in non-alphabetical order\ldots)
\begin{align}
p_\xi &= s \\
s_\xi &= \lambda p - c s - K_u p - K_v q \\
q_\xi &= r \\
r_\xi &= (\lambda q - c r - K_u p - K_v q)/\epsilon
\end{align}
Writing the system as $X' = AX$, where $K_u$ and $K_v$ depend on the front,
\[
X = \begin{bmatrix}p\\s\\q\\r\end{bmatrix},
A = \begin{bmatrix}
0 & 1 & 0 & 0 \\
\lambda - K_u & -c & -K_v & 0 \\
0 & 0 & 0 & 1 \\
- K_u/\epsilon & 0 & (\lambda - K_v)/\epsilon & - c / \epsilon
\end{bmatrix}
\]
\section{Eigenvalues}
\subsection{$\epsilon = 0$}
\subsubsection{$+\infty$}
At $(u,v) = 0$, we have $K_u = K_v = 0$, so this simplifies to
\[
A = \begin{bmatrix}
0 & 1 & 0 \\
\lambda & -c & 0 \\
0 & 0 & \lambda/c
\end{bmatrix}
\]
This has eigenvalues $(-c \pm \sqrt{c^2 + 4 \lambda})/2$ and $\lambda/c$. For $\Re \lambda > 0$, the one with negative real part is
\[\lambda_1 = \frac{-c - \sqrt{c^2 + 4 \lambda}}{2}\]
One eigenvector for it is
\[v_1 = [1,(-c - \sqrt{c^2 + 4 \lambda})/2,0] = [1,\lambda_1,0] \]
\subsubsection{$-\infty$}
At $(u,v) = (1,1)$ we get
\[
A = \begin{bmatrix}
0 & 1 & 0 \\
\lambda & -c & e^{(1-h)Z} \\
0 & 0 & (\lambda + e^{(1-h)Z})/c
\end{bmatrix}
\]
with eigenvalues $(-c \pm \sqrt{c^2 + 4 \lambda})/2$ and $(\lambda + e^{(1-h)Z})/c$.
We're actually interested in the adjoint $-A^T$, whose eigenvalues are the negation of those.
Thus, the unique positive eigenvalue is
\[\lambda_2 = \frac{c + \sqrt{c^2 + 4 \lambda}}{2} = -\lambda_1 \]
One eigenvector (of $-A^T$) for that is
\[
v_2 = \left[1, -\frac{c + \sqrt{c^2 + 4 \lambda}}{2\lambda}, \frac{(c + \sqrt{c^2+4\lambda})}{\lambda e^{Z(h-1)}(c + \sqrt{c^2+4\lambda} + 2 \lambda/c)+ 2 \lambda / c}\right]
\]
\subsection{$\epsilon \neq 0$}
\subsubsection{$+\infty$}
At $(u,v) = 0$, we have $K_u = K_v = 0$, so this simplifies to
\[
A = \begin{bmatrix}
0 & 1 & 0 & 0 \\
\lambda & -c & 0 & 0 \\
0 & 0 & 0 & 1 \\
0 & 0 & \lambda /\epsilon & - c / \epsilon
\end{bmatrix}
\]
The eigenvalues with negative real part are:
\begin{align*}
\lambda_1 &= -\frac{1}{2} (c + \sqrt{c^2 + 4 \epsilon \lambda})/\epsilon\\
\lambda_2 &= -\frac{1}{2} (c + \sqrt{c^2 + 4 \lambda})
\end{align*}
Their respective eigenvectors are:
\begin{align*}
v_1 &= [0,0,1,-\frac{1}{2} (c + \sqrt{c^2 + 4 \epsilon \lambda})/\epsilon] = [0,0,1,\lambda_1] \\
v_2 &= [1, -\frac{1}{2} (c + \sqrt{c^2 + 4 \lambda}), 0, 0] = [1,\lambda_2,0,0]
\end{align*}
We actually need the two with positive real part as well, in order to use the Wronskian to test for mode mixing.
\begin{align*}
\lambda_3 &= -\frac{1}{2} (c - \sqrt{c^2 + 4 \epsilon \lambda})/\epsilon\\
\lambda_4 &= -\frac{1}{2} (c - \sqrt{c^2 + 4 \lambda})
\end{align*}
Their associated eigenvectors are:
\begin{align*}
v_3 &= [0,0,1,\lambda_3] \\
v_4 &= [1,\lambda_4,0,0]
\end{align*}
\subsubsection{$-\infty$}
At $(u,v) = (1,1)$, we have $K_u = 0$ and $K_v = -e^{(1-h)Z}$.
The matrix becomes:
\[
A = \begin{bmatrix}
0 & 1 & 0 & 0 \\
\lambda & -c & e^{(1-h)Z} & 0 \\
0 & 0 & 0 & 1 \\
0 & 0 & (\lambda + e^{(1-h)Z})/\epsilon & - c / \epsilon
\end{bmatrix}
\]
%Again, we look for eigenvalues and eigenvectors of $-A^T$, and choose positive real part.
We look for eigenvalues with positive real part. In this case, we don't work with the adjoint.
We follow the method from Lafortune, Lega, and Madrid.
The first eigenvector is particularly horrific.
It might be worth seeing if another CAS can produce a simpler version, maybe by writing it in terms of the eigenvalue.
\begin{align*}
\nu_1 &=-1/2 \left(c e^{Z h - Z} - \sqrt{(c^2 + 4 \epsilon \lambda) e^{2 Z h - 2 Z} +
4 \epsilon e^{Z h - Z}}\right) e^{-Z h + Z}/\epsilon
\\
\nu_2 &= -1/2 c + 1/2 \sqrt{c^2 + 4 \lambda}
\end{align*}
\begin{align*}
w_1 =& [1, ((\sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} c \epsilon - \sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} c) e^{3/2 Z h} \\
& \quad - (c^2 \epsilon - c^2 -
2 \epsilon \lambda) e^{2 Z h} + 2 \epsilon e^{Z h + Z})/(\sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} \epsilon e^{3/2 Z h} \\
& \quad + (2 c \epsilon^2 -
c \epsilon) e^{2 Z h}), \\
&\!-1/2 (c^2 \epsilon e^{3 Z h - Z} - c^2 e^{3 Z h - Z} -
((\sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon \lambda e^{2 Z h - 2 Z} + 4 \epsilon e^{Z h
- Z}} c + 2) \epsilon \\
& \quad - \sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon \lambda e^{2 Z h -
2 Z} + 4 \epsilon e^{Z h - Z}} c) e^{2 Z h} + 2 (\epsilon^2 e^{3 Z h - Z} -
\epsilon e^{3 Z h - Z}) \lambda) e^{-2 Z h}/\epsilon^2, \\
& 1/2 (2 c \epsilon^2 +
(\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} e^{-1/2 Z h} -
3 c) \epsilon \\
& \quad - (\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h} +
4 \epsilon e^Z} c^2 \epsilon e^{-Z h - Z} - \sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} c^2 e^{-Z h - Z} \\
& \quad + (\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} \epsilon^2 e^{-Z h - Z} - \sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} \epsilon e^{-Z h - Z}) \lambda) e^{3/2 Z h} \\
& \quad + (c^3 \epsilon e^{-Z h -
Z} - c^3 e^{-Z h - Z} + 3 (c \epsilon^2 e^{-Z h - Z} - c \epsilon e^{-Z h -
Z}) \lambda) e^{2 Z h})/\epsilon^3]
\\
w_2 =& [1, \nu_2, 0, 0]
\end{align*}
We also need the eigenvalues with negative real part, for the Wronskian mode-mixing test.
\begin{align*}
\nu_3 &=-1/2 \left(c e^{Z h - Z} + \sqrt{(c^2 + 4 \epsilon \lambda) e^{2 Z h - 2 Z} +
4 \epsilon e^{Z h - Z}}\right) e^{-Z h + Z}/\epsilon
\\
\nu_4 &= -1/2 c - 1/2 \sqrt{c^2 + 4 \lambda}
\end{align*}
\begin{align*}
w_3 =& [1, ((\sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} c \epsilon - \sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} c) e^{3/2 Z h} \\
& \quad + (c^2 \epsilon - c^2 -
2 \epsilon \lambda) e^{2 Z h} - 2 \epsilon e^{Z h + Z})/(\sqrt{c^2 e^{Z h} +
4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} \epsilon e^{3/2 Z h} \\
& \quad - (2 c \epsilon^2 -
c \epsilon) e^{2 Z h}), \\
&\!-1/2 (c^2 \epsilon e^{3 Z h - Z} - c^2 e^{3 Z h - Z} +
((\sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon \lambda e^{2 Z h - 2 Z} + 4 \epsilon e^{Z h
- Z}} c - 2) \epsilon \\
& \quad - \sqrt{c^2 e^{2 Z h - 2 Z} + 4 \epsilon \lambda e^{2 Z h -
2 Z} + 4 \epsilon e^{Z h - Z}} c) e^{2 Z h} + 2 (\epsilon^2 e^{3 Z h - Z} -
\epsilon e^{3 Z h - Z}) \lambda) e^{-2 Z h}/\epsilon^2, \\
& 1/2 (2 c \epsilon^2 -
(\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h} + 4 \epsilon e^Z} e^{-1/2 Z h} +
3 c) \epsilon \\
& \quad + (\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h} +
4 \epsilon e^Z} c^2 \epsilon e^{-Z h - Z} - \sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} c^2 e^{-Z h - Z} \\
& \quad + (\sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} \epsilon^2 e^{-Z h - Z} - \sqrt{c^2 e^{Z h} + 4 \epsilon \lambda e^{Z h}
+ 4 \epsilon e^Z} \epsilon e^{-Z h - Z}) \lambda) e^{3/2 Z h} \\
& \quad + (c^3 \epsilon e^{-Z h -
Z} - c^3 e^{-Z h - Z} + 3 (c \epsilon^2 e^{-Z h - Z} - c \epsilon e^{-Z h -
Z}) \lambda) e^{2 Z h})/\epsilon^3]
\\
w_4 =& [1, \nu_4, 0, 0]
\end{align*}
\section{Evans function}
\subsection{$\epsilon = 0$}
We perform two integrations.
These depend on a fixed front, a solution of the ODE \eqref{front_eps0}.
We pick left, middle, and right points $L, M, R$, along this front.
The left endpoint is just the point we started shooting from (in our implementation, $\xi=0$).
Currently, we pick the middle as the first point where the average of $u$ and $v$ is below 0.3,
and the right is the first point where $u < 0.001$.
These are somewhat arbitrary.
As $\xi$ changes during the integration, the front gives us different values of $u,v$ in $A$.
We integrate $X' = AX$ from $\xi = R$ to $M$, with initial condition $e^{\lambda_1 (R-M)}v_1$.
We integrate $X' = -A^T X$ from $L$ to $M$, with initial condition $e^{\lambda_1 (M-L)}v_2' = e^{-\lambda_2 (M-L)}v_2'$. The vector $v_2'$ is another eigenvector collinear with $v_2$, but normalized so that $v_1 \cdot v_2' = 1$.
\[v_2' = \frac{v_2}{v_2 \cdot v_1}\]
The Evans function is the dot product of these results at $\xi = M$.
(being careful to do this the correct way: \verb|a.' * b| is what we want,
not \verb|dot(a,b)|, which does \verb|a' * b|)
\end{document}